POLEMIK POLITIK IDENTITAS DI INDONESIA - Maghfira Faraidiany; Novita Sari; Siti hardiyanti (Journal of Political Sphere, 2022)
The phenomenon of identity politics has been highlighted since the New Order era. Identity politics is a political practice based on ethnic, racial, religious and socio-cultural similarities. Identity politics often appears ahead of the people's democratic party. The presence of identity politics is one of the triggers for conflict in society, such as political feuds that occur between minority and majority groups. This has seriously injured the constellation of democracy in Indonesia. The research method used in this research is descriptive research with a qualitative approach. Through research methods of collecting library data (library research). The results of the study show that identity politics occurs as a form of domination by certain groups over their interests, identity politics is closely related to ethnicity, religion, ideology and local interests which are generally represented. The conclusion of this study can be said that identity politics is studied from two categories, the positive and negative sides. From the positive side, identity politics is a form of tolerance for differences in religion, race and culture so that conflicts can be mitigated. from the negative side, identity politics as a form of group division over differences.